Total Family Risk of Families of school adolescents from a Vulnerable Area of North Lima - Asencios-Trujillo, Lucia; Asencios-Trujillo, Lida; Gallegos-Espinoza, Djamila; Piñas-Rivera, Livia (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
Family risk is one of the probabilities in which adverse situations may occur within the family that can be witnessed during a family assessment, so the research objective is to determine the total family risk of families with school adolescents in a vulnerable area of North Lima. It is a quantitative, descriptive-transversal study, with a total population made up of 140 heads of household with school adolescents who answered a questionnaire on sociodemographic aspects and the instrument of total family risk. In the results, it can be observed that 62,9 % (n=88) of the heads of household have a family with low risk, 27,1 % (n=38) have threatened families and 10 % (n=14) have families with high risk. In conclusion, the strengthening of health professionals in terms of extramural work is very important because it allows to identify if there is any risk that compromises the family, especially the infant, and to be able to act according to the situation.